2012
DOI: 10.1200/jop.2011.000268
|View full text |Cite
|
Sign up to set email alerts
|

Hemoglobin Trends and Anemia Treatment Resulting From Concomitant Chemotherapy in Community Oncology Clinics

Abstract: Purpose: This study describes changes in hemoglobin (Hb) levels in patients during chemotherapy before anemia treatment and in those who received no treatment, measuring time from chemotherapy initiation to Hb less than 10 g/dL and anemia treatment initiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 18 publications
2
14
0
Order By: Relevance
“…Henry et al showed that the number of ESA administrations per patient decreased from a mean of 4.6 to 2.9 following the NCD, nearly identical to our results. Previous studies have reported a decrease in mean Hb levels and the proportion of patients with Hb > 10 g/dL at the time of treatment initiation, findings that are in agreement with our oncology EMR database results. However, these previous studies examined that smaller study populations and fewer tumor types had shorter follow‐up periods and generally were less geographically representative .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Henry et al showed that the number of ESA administrations per patient decreased from a mean of 4.6 to 2.9 following the NCD, nearly identical to our results. Previous studies have reported a decrease in mean Hb levels and the proportion of patients with Hb > 10 g/dL at the time of treatment initiation, findings that are in agreement with our oncology EMR database results. However, these previous studies examined that smaller study populations and fewer tumor types had shorter follow‐up periods and generally were less geographically representative .…”
Section: Discussionsupporting
confidence: 92%
“…Our results are consistent with prior studies showing decreases in ESA use and increases in transfusion use following the ESA label change and subsequent NCD. Henry et al showed that the number of ESA administrations per patient decreased from a mean of 4.6 to 2.9 following the NCD, nearly identical to our results.…”
Section: Discussionmentioning
confidence: 95%
“…If, in the post‐NCD period, practice patterns changed such that hemoglobin thresholds at which transfusions are given to chemotherapy‐treated cancer patients decreased, a tendency toward increased transfusions in the post‐NCD period would be blunted. Although lower hemoglobin levels among chemotherapy‐treated cancer patients post‐NCD have been reported, the one published report we are aware of regarding hemoglobin levels at transfusion reports no significant difference pre‐NCD/post‐NCD …”
Section: Discussionmentioning
confidence: 77%
“…Interpreting this study's results is difficult because adjustments were not made for pre‐NCD/post‐NCD differences in the patient populations receiving ESAs. Finally, a second study involving Georgia Cancer Specialists chemotherapy‐treated cancer patients compared ESA and transfusion use in 2006 and 2009 . Calculations from results of this study of patients of all ages and all cancer types indicate that ESA use decreased from 52.0% in 2006 to 13.5% in 2009, and transfusion use increased from 10.0% to 10.7% (relative increase, 7%).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation